Advances in coastal modeling - Lakhan, V. C. (Elsevier, 2003)
This book unifies and enhances the accessibility of contemporary scholarly research on advances in coastal modeling. A comprehensive spectrum of innovative models addresses the wide diversity and multifaceted aspects of coastal research on the complex natural processes, dynamics, interactions and responses of the coastal supersystem and its associated subsystems. The twenty-one chapters, contributed by internationally recognized coastal experts from fourteen countries, provide invaluable insights on the recent advances and present state-of-the-art knowledge on coastal models which are essential for not only illuminating the governing coastal process and various characteristics, but also for understanding and predicting the dynamics at work in the coastal system.
Keywords: Coast changes -- Mathematical models.; elektronické knihy; electronic books